Low cycle fatigue behaviour of additive manufactured maraging steel: Influence of build orientation and heat treatment - Vishwakarma J.; Rajpurohit R.S.; Sudhakar Rao G.; Chattopadhyay K.; Santhi Srinivas N.C. (My University, 2025)
The effect of build orientation and heat treatment (solution treatment and aging) on low cycle fatigue (LCF) behaviour of additive manufactured (AM) maraging steel, processed via powder bed fusion, using laser beam (PBF-LB) was investigated in the present work. The build orientation has significant influence on LCF behaviour of AM maraging steel. Un-melted defects were found to be the most detrimental to fatigue life. Defects in 90° oriented samples were more damaging than those in 45° and 0° oriented samples. Heat treatment (HT) of the AM maraging steel was found to be very effective in enhancing the fatigue life by 8–10 times due to marked strengthening by precipitation of intermetallic precipitates and reduction in size and number of AM defects. SEM fractography showed that surface and interior flaws increased susceptibility to crack propagation through the cross-section. © 2023 Elsevier B.V.